Study of Thyroid Hormone Levels Among Patients With Type 2 Diabetes Mellitus Attending a Tertiary Care Hospital of Chattogram, Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: In diabetic individuals, undiagnosed thyroid function abnormalities may increase the risk of cardiovascular disease and affect metabolic management. Screening procedures, however, differ greatly, and there are no practical guidelines. The study aimed to find out the pattern and related factors of thyroid dysfunction in patients with Type-2 Diabetes Mellitus (T2DM) in a tertiary care hospital of Chattogram, Bangladesh, compared to the apparently healthy individuals.Materials and methods: This comparative cross-sectional study compares, 50 diagnosed patients at Chittagong Medical College Hospital with T2DM were enrolled between January 2022 to December 2022 and 50 healthy individuals living in Chattogram City were selected as controls. Participants were screened for thyroid function test by estimating serum Thyroid Stimulating Hormone (TSH) Free Thyroxine (FT4) Free Tri-iodothyronine (FT3).Results: The mean age of patients with T2DM was 45.5±6.2 years with a mean duration of diabetes of 5.2 ±1.6 years and 62% were female. Mean TSH level was higher in T2DM group contrasted to control group (3.51±0.42 vs. 2.47±0.23 µIU/ml, p=0.034). Mean serum FT3 and FT4 levels were similar in two groups (p=0.11 and p=0.56, respectively). Twelve (24%) of the patients with T2DM had thyroid function abnormalities (Overt hypothyroidism 6%, and subclinical hypothyroidism 18%) compared to 4% in the control group (p=0.013). Compared to non-T2DM subject, T2DM patients had 7.61 times higher chance of having thyroid function abnormalities (Odds ratio: 7.61, 95% confidence interval: 1.56-37.17, p=0.012). Duration of diabetes (r=0.388, p=0.005) and HbA1C levels (r=0.552, p=